The Relation between Exercise Duration and Intensity on Phosphocreatine (PCr) Level: an Article Review - Aprilia Durotun Nasikhah1 , Roy Januardi Irawan2 , Trias Mahmudiono3* (Indian Journal of Forensic Medicine & Toxicology, 2021)
Exercise is a physical activity that planned, structured, and sustainable. Exercise has 4 criteria, that isfrequency, intensity, type, and duration. During exercise, phosphocreatine (PCr) depletion increases, andearly intracellular acidosis has occurred. These changes contribute to a decrease in training capacity interms of training duration. This literature review aimed to determine the relationship between the intensityand duration of exercise with the concentration of PCr and recovery factors. The literature study has carriedout by selecting an Experiment research design. The results of the review showed that PCr was the largestenergy contributor in the first 10 seconds of exercise in the heavy-intensity exercise where phosphocreatinetriggers energy without oxygen or anaerobic. The recovery of PCr influenced by a person’s health conditionand age. The concentration of PCr in children was higher than in adults because of the relatively high rateof oxidative ATP formation. It proved that there was a significant relationship between PCr and the durationand intensity of exercise.